RETROFIT GAS LIFT A PRACTICAL SOLUTION TO INCREASE PRODUCTION - Zikrina Khairun Nissa; Rachmat Sudibjo; Kartika . (Lembaga Penelitian Universitas Trisakti, 2015)
The purpose of this final assignment is to introduce an alternative new method of unconventionalgas lift which also the first implementation done in Indonesia by ConocoPhillips Indonesia on theirwells in North Belut, Natuna. though, artificial-lift technology is well established, alternativemethods or new developments continue to play a role in solving problems and meeting productionchallenges. This final assignment will also describe the specific and detailed systems of thismethod, so hopefully the wells with this method could produce to its fully potential.